Endogenous GLP-1 levels play an important role in determining the efficacy of DPP-IV Inhibitors in both prediabetes and type 2 diabetes - Chong, Shiau Chin; Sukor, Norlela; Robert, Sarah Anne; Ng, Kim Fong; Kamaruddin, Nor Azmi (Frontiers in Endocrinology, 2022)
Background: In contrast to Western population, glucagon-like peptide-1 (GLP-1) levels are preserved in some East Asian population with type 2 diabetes (T2D), explaining why dipeptidyl peptidase-IV (DPP-IV) inhibitors are more effective in East Asians. We assessed whether differences in endogenous GLP-1 levels resulted in different treatment responses to DPP-IV inhibitors in prediabetes and T2D. Methods: A prospective 12-week study using linagliptin 5mg once daily in 50 subjects (28 prediabetes and 22 T2D) who were stratified into high versus low fasting GLP-1 groups. A 75-g oral glucose tolerance test (OGTT) was performed at week 0 and 12. Primary outcomes were changes in HbA1c, fasting and post-OGTT glucose after 12 weeks. Secondary outcomes included changes in insulin resistance and beta cell function indices. Results: There was a greater HbA1c reduction in subjects with high GLP-1 compared to low GLP-1 levels in both the prediabetes and T2D populations [least-squares mean (LS-mean) change of -0.33% vs. -0.11% and -1.48% vs. -0.90% respectively)]. Linagliptin significantly reduced glucose excursion by 18% in high GLP-1 compared with 8% in low GLP-1 prediabetes groups. The reduction in glucose excursion was greater in high GLP-1 compared to low GLP-1 T2D by 30% and 21% respectively. There were significant LS-mean between-group differences in fasting glucose (-0.95 mmol/L), 2-hour glucose post-OGTT (-2.4 mmol/L) in the high GLP-1 T2D group. Improvement in insulin resistance indices were seen in the high GLP-1 T2D group while high GLP-1 prediabetes group demonstrated improvement in beta cell function indices. No incidence of hypoglycemia was reported. Conclusions: Linagliptin resulted in a greater HbA1c reduction in the high GLP-1 prediabetes and T2D compared to low GLP-1 groups. Endogenous GLP-1 level play an important role in determining the efficacy of DPP-IV inhibitors irrespective of the abnormal glucose tolerance states.